Dr. Richard Barton — Deep Plane Facelift — Melbourne - Barton, Richard (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Richard Barton, practicing in Melbourne, Australia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003084; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; australia; melbourne